A Multiband Transparent Transponder Based on Reconfigurable Optical Frequency Combs for Cross Connection of Intersatellite and Satellite Ground - Bin Wu; Hongxi Yin; Anliang Liu; Xiuyang Ji; Qingchun Zhao (IEEE Photonics Journal, 2018)
In this paper, a parallel multiband frequency-conversion scheme for satellite applications based on a single optical frequency comb is proposed, and a reconfigurable satellite transponder is designed for future multiband broadband satellites. In addition, we establish a test system of onboard multiband frequency-conversion on the strength of microwave photonics and, a proof-of-concept experiment is demonstrated in which a Ka-band signal is converted to other satellite frequency bands. The experimental results reveal our system feasibility, and the bit error rate of recovered baseband data is less than 10–9. Moreover, the optical frequency combs can be reconfigured by adjusting the parameters of the local oscillator and optical modulator.